RASIONALISME MASYARAKAT INTERNASIONAL DALAM SAINS DAN TEKNOLOGI: STUDI KASUS INISIATIF AMERIKA SERIKAT DALAM INTERNATIONAL SPACE STATION PROGRAM DI TAHUN 1998 - Yuliana Putri Rahmadani; Syafri Harto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Many nations have developed their potency and capacity of space science and technology. This happened due to the assumption of Space as neutral territory and it is free to be explored. Moreover, as its nature that still provides mystery. International Space Station (ISS) then created to accommodating nations curiosity related to science and technology of space. ISS is a laboratory in Earth Orbit. It’s Zero Gravity condition that makes it ideal to conduct a lot of research that could not be on Earth which have a lot of benefit for man. ISS is made by international cooperation of United States of America, Canada, Japan, Russia and Europe Union. America indeed is the initiator of ISS. Through this research, it will be identified deeply rationalization of America behind its contribution to ISS building.This research is an explanative research which intends to explain phenomenon or issue in International Relations. Library Research method is used through primary and secondary sources from Books, Website, and Journals that mostly obtained from NASA’s and USA’s Government.This research as well would explain linkages of independent and dependent variable so the result of the research could be understood. That America’s Commitment to international cooperation of space science and technology along Its eagerness to making ‘peace’ with Russia after Cold War have been succeeded in creating ISS especially by their precidential pro-science policies including Gore-Chernomyrdin Commission.Keywords: International Space Station (ISS), Big Science, Rationalism, International Society, English School